# Factorising quadratics - (easy) **Example 3**

Factorise the quadratic `x^2-x-6=0`

The factors of `-6` are:

1 and 6

2 and 3

Now ask yourself what factors of c equal b.

i.e. What factors of `-6` add to give `-1`

`-3+2=-1` and `-3times2=-6`

Therefore:

`x^2-x-6=0`

Can be written as:

`(x-3)(x+2)=0`

Check by multiplying out

The roots of `x^2-x-6=0`

are `(x-3)=0`

and `(x+2)=0`

Now solve for `x`

`x=3` or `x=-2`

**Answer:**

The roots of `x^2-x-6=0` are `x=3` or `x=-2`

# Factorising quadratics - (easy) **Example 3**

Factorise the quadratic `x^2-x-6=0`

The factors of `-6` are:

1 and 6

2 and 3

Now ask yourself what factors of c equal b.

i.e. What facors of `-6` add to give `-1`

`-3+2=-1` and `-3times2=-6`

Therefore:

`x^2-x-6=0`

Can be written as:

`(x-3)(x+2)=0`

Check by multiplying out

The roots of `x^2-x-6=0`

are `(x-3)=0`

and `(x+2)=0`

Now solve for `x`

`x=3` or `x=-2`

**Answer:**

The roots of `x^2-x-6=0` are `x=3` or `x=-2`